Inclusive leadership and work engagement: the mediating role of procedural justice. Issue 1 (20th July 2020) - Cenkci, Ada Tuna; Bircan, Tuba; Zimmerman, Jeff
Abstract : Purpose: This paper aims to explore the relationship between inclusive leadership (IL) and employee work engagement (WE), as well as the mediating effect of procedural justice (PJ) on this relationship. Design/methodology/approach: An online, self-administered questionnaire was used to collect data. A total of 201 information technology (IT) professionals in Turkey participated in the study. The authors used structural equation modeling to analyze the collected data. The authors then used a series of nested model comparisons to test the hypothesized mediating relationship. Findings: The outcomes suggest that IL is positively related to PJ while PJ is positively associated with WE. In addition, PJ mediates the relationship between IL and WE. Practical implications: The outcomes underline the importance of IL to effectively lead IT professionals. Organizational leaders can cultivate IL by demonstrating openness, availability and accessibility toward their employees and create work environments in which employees' ideas are valued. Additionally, for employee PJ perceptions, organizations need to ensure that their procedures and policies are transparent and fair in terms of how decisions are made. Moreover, organizations can offer training to their IT managers on IL and PJ topics. Originality/value: This study adds to the very scarce literature on IL. In addition, to the researchers' knowledge, this is the first study to test the IL and PJ relationship. Furthermore, this is the first study to explore the concept of IL in the Turkish context. Moreover, the findings of this research can be beneficial for future theory development on IL in cross-cultural contexts.